A prospective study of functional outcome of treatment of intra-articular fracture of proximal interphalangeal joint by static traction and early mobilization in adults - Ameya H. Velankar; Ashok M. Ghodke; Sanjeev Kumar Singh (MGM Journal of Medical Sciences)
Background: Failure to appropriately address intra-articular fractures of the proximal interphalangeal (PIP) joint may result in enduring pain, stiffness, and post-traumatic arthritis. Our approach employs a straightforward and economical method of creating a static traction splint using an aluminum splint. This splint is removed after 2 weeks, followed by the initiation of early mobilization. Materials and Methods: A flexible aluminum splint is placed on the injured finger. A polypropylene suture passes through the nail and is tied to the splint for sustained traction, and the finger is immobilized for 2 weeks. After this period, the splint is removed, and active assisted finger mobilization begins. Patients are assessed post-surgery using the Ishida score. Results: This study involved 30 treated patients, with a mean age of 31.47 ± 11.11 years, ranging from 18 to 69 years. Among them, 26 were male and 4 were female, with 20 experiencing right-side involvement. Sports-related injuries were reported in 17 cases, followed by road traffic accidents in 7 cases and slips in 6 cases. The mean range of motion, measured in degrees, was 83.3 ± 0.22. Overall, the patients achieved excellent results. Conclusion: Utilizing static traction for intra-articular PIP joint fractures is a safe, relatively straightforward, and cost-effective method with minimal complications. This approach guarantees anatomical joint alignment, promotes favorable fracture healing, and facilitates early mobilization, leading to a swift and satisfactory recovery.